Dwór Artusa - piwnice / Foto mgr Karol Nowaliński. - Nowaliński, Karol (1935- ). (Foto mgr Karol Nowaliński ul. Mickiewicza, 1990)
Przedstawia dwa ujęcia piwnic w Dworze Artusa w trakcie remontu, około 1992 roku.